Perinatal MRI diffusivity is related to early assessment of motor performance in preterm neonates - Navarra, Riccardo (Neuroradiol J, 2016)
Preterm neonates represent a high-risk population for abnormal neuropsychological development. But presently, an accurate method for identifying those at risk is not available. This study evaluated the association between the microstructural organization measured with Diffusion Tensor Imaging (DTI) in term-corrected preterm neonates and subsequent motor performance. Fractional anisotropy (FA), axial diffusion (AD), mean diffusivity (MD) and radial diffusivity (RD) were determined in two regions of interest (ROIs) corresponding to the posterior limb of the internal capsule (PLIC) and cortico-spinal tract (CST). The Griffiths Mental Developmental Scales (GMDS) were longitudinally administered at 3, 6 and 15 months; and correlations between the metrics of diffusivity and the motor subscale of the GMDS were assessed using the Spearman correlation. A statistically significant negative correlation was observed between the AD of PLIC of the left hemisphere and the 3-month GMDS Locomotor Subscale. These results suggested that AD is a valid indicator of the stage of maturation of the motor pathway in preterm neonates, but not of later motor outcome.